A case report of tuberculous constrictive pericarditis as a sole manifestation of tuberculosis in a male adolescent (Faculty of Medicine Universitas Indonesia, 2022)
Constrictive pericarditis is a rare type of pericardial disease that can be caused by various factors. Tuberculosis (TB) is one of the most common causes of this abnormality in Indonesia. Interestingly, tuberculous constrictive pericarditis can occur in the absence of acute pericarditis, pulmonary, or extrapulmonary TB. This case described a male adolescent with refractory right-sided heart failure symptoms who developed a rapidly progressive tuberculous constrictive pericarditis. Various imaging modalities, such as echocardiography, chest computed tomography (CT) scan, cardiac magnetic resonance imaging, and incidental PET/CT scan, were used to diagnose the pericardial abnormality. Histopathological findings in pericardial tissues confirmed the diagnosis. Complete surgical pericardiectomy, in conjunction with anti-TB drugs, diuretics, and colchicine, resulted in a significant clinical improvement.